Investigating the normalization and normative views of gestational weight gain: Balancing recommendations with the promotion and support of healthy pregnancy diets. Issue 5 (6th May 2021) - Moffat, Tina; McKerracher, Luseadra; Oresnik, Sarah; Atkinson, Stephanie A.; Barker, Mary; McDonald, Sarah D.; Murray‐Davis, Beth; Sloboda, Deborah M.
Abstract: Objectives: Gestational weight gain (GWG) is increasingly monitored in the United States and Canada. While promoting healthy GWG offers benefits, there may be costs with over‐surveillance. We aimed to explore these costs/benefits. Methods: Quantitative data from 350 pregnant survey respondents and qualitative focus group data from 43 pregnant/post‐partum and care‐provider participants were collected in the Mothers to Babies (M2B) study in Hamilton, Canada. We report descriptive statistics and discussion themes on GWG trajectories, advice, knowledge, perceptions, and pregnancy diet. Relationships between GWG monitoring/normalization and worry, knowledge, diet quality, and sociodemographics—namely low‐income and racialization—were assessed using χ 2 tests and a linear regression model and contextualized with focus group data. Results: Most survey respondents reported GWG outside recommended ranges but rejected the mid‐20th century cultural norm of "eating for two"; many worried about gaining excessively. Conversely, respondents living in very low‐income households were more likely to be gaining less than recommended GWG and to worry about gaining too little. A majority had received advice about GWG, yet half were unable to identify the range recommended for their prepregnancy BMI. This proportion was even lower for racialized respondents. Pregnancy diet quality was associated with household income, but not with receipt or understanding of GWG guidance. Care‐providers encouraged normalized GWG, while worrying about the consequences of pathologizing "abnormal" GWG. Conclusions: Translation of GWG recommendations should be done with a critical understanding of GWG biological normalcy. Supportive GWG monitoring and counseling should consider clinical, socioeconomic, and community contexts.